An NBD Derivative of the Selective Rat Toxicant Norbormide as a New Probe for Living Cell Imaging - D'Amore, Claudio; Orso, Genny; Fusi, Fabio; Pagano, Mario A.; Miotto, Giovanni; Forgiarini, Alessia; De Martin, Sara; Castellani, Giulia; Ribaudo, Giovanni; Rennison, David; Brimble, Margaret A.; Hopkins, Brian; et al. (Frontiers in Pharmacology, 2016)
Norbormide (NRB) is a unique compound that acts directly on rat vascular myocytes to trigger a contractile process, through an as yet unknown mechanism, which results in the selective contraction of rat peripheral arteries. To gain insight into the mechanisms involved in NRB rat-selective activity, we investigated the subcellular distribution of NRB-AF12, a nitrobenzodiazole (NBD)-derivative of NRB, in living NRB-sensitive and NRB-insensitive cells. In both cell types, NRB-AF12 localised to the endoplasmic reticulum (ER), Golgi apparatus, mitochondria, lysosomes and endosomes; however, in NRB-sensitive cells, the fluorescence also extended to the plasma membrane. NRB-AF12 was rapidly internalised into the cells, could easily be washed out and then reloaded back into the same cells, all with a high degree of reproducibility. Cells exposed for 24 h to NRB-AF12 did not show apparent signs of toxicity, even at concentrations of the dye (10 µM) much higher than those required for fluorescence labelling (500 ηM). The distribution pattern of NRB-AF12 fluorescence was near identical to that of ER-Tracker® (Er-Tr), a fluorescent derivative of glibenclamide, a known KATP channel blocker. Displacement tests did not demonstrate, but at the same time did not rule out the possibility of a common target for ER-Tr, NRB-AF12, NRB and glibenclamide. On the basis of these results we hypothesize a common target site for NRB-AF12 and ER-Tr, and a similar target profile for norbormide and glibenclamide, and propose NRB-AF12 as an alternative fluorescence probe to ER-Tracker. Furthermore, NRB-based fluorescence derivatives could be designed to selectively label single cellular structures.